Online social networks and corporate investment similarity - Jing, Wei; Zhang, Xueyong (Journal of Corporate Finance, 2021)
This paper analyzes the relationship between online social networks and inter-firm investment similarity. Using mutual friendships of senior officers on Sina Weibo as proxies for online social connections, we find that companies, whose senior officers share online connections, exhibit more similar levels of capital investments. In addition, the baseline result is robust in subsamples of senior officers' first like on Weibo, and continue to hold for a battery of robustness and endogeneity tests. One possible underlying mechanism through which social networks influence corporate investment similarity is that senior officers learn privileged information from their social connections, which is supported by examining the interaction effect of analyst coverage and online social connections. We further show that this investment similarity is more pronounced in the condition that company pairs are connected by more reputable senior officers, or in the case of under-investing.